Na genologicznych manowcach - "Zwierciadło dla panien zakonnych" = On the genological byways - "A Mirror For Nuns" - Klimek-Grądzka, Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the handwritten "Mirror for Nuns" (Zwierciadło dla panien zakonnych) from the resources of the Jagiellonian Library and, based on the title and macrostructure of the text, attempts to determine its genre classification. It has been established that the text aligns with the monastic rule, albeit an atypical one, as it does not fully adhere to the characteristics of the prototypical genre. The personal ideal of a nun, as depicted in the "Mirror", positions it within the canon of parenetic discourse and, due to its persuasiveness, presents an anti-ideal and the consequences of acting contrary to the recommendations of the rule.
Keywords: reguła zakonna; rękopis; stylistyka; genologia; monastic rule; manuscript; stylistics; genre theory